The Use of Tests as Tools for Psychomotor Intervention: its Value in the Analysis of the Psychomotor Structure - de Pena, Lucía; Diez, Mariana (Revista de Investigación en Logopedia, 2021)
The tests have been used as instruments for assessing different components of the psychomotor structure from the origins of psychomotor skills as a discipline and as a profession. This practice has been consolidated in all areas of intervention and in all age groups, so that the generalization in its use requires deep levels of analysis regarding the underlying technical and ethical considerations. We propose to discuss its value for the analysis of the psychomotor structure in order to recognize its potential, while pointing out its limitations and controversies. The information that the tests show carries a value that can only be assigned in its articulation with the analysis of all the elements of the psychomotor structure, while we understand psychomotor work as the projection that emerges from the intersection of neurobiological equipment, experiences with a significant other and the discourses around the body.
Keywords: Psychomotor assessment; Psychomotor structure; Tests